2020
DOI: 10.1101/2020.08.26.266320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural signatures of attentional engagement during narratives and its consequences for event memory

Abstract: As we comprehend narratives, our attentional engagement fluctuates over time. Despite theoretical conceptions of narrative engagement as emotion-laden attention, little empirical work has characterized the cognitive and neural processes that comprise subjective engagement in naturalistic contexts or its consequences for memory. Here, we relate fluctuations in narrative engagement to patterns of brain coactivation, and test whether neural signatures of engagement predict later recall. In behavioral studies, par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 97 publications
(116 reference statements)
0
16
2
Order By: Relevance
“…We correlated 1) the mean between-movie boundary pattern during recall and 2) the mean within-movie event boundary pattern during encoding, in PMC (Figure 4, ‘Event offset’ condition). Surprisingly, the two were negatively correlated ( t (14) = 5.10, p < .001, Cohen’s d z = 1.32), suggesting that the between-movie boundary pattern may reflect a cognitive state qualitatively different from the state elicited by event boundaries during movie watching (e.g., attentional engagement; Song et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
“…We correlated 1) the mean between-movie boundary pattern during recall and 2) the mean within-movie event boundary pattern during encoding, in PMC (Figure 4, ‘Event offset’ condition). Surprisingly, the two were negatively correlated ( t (14) = 5.10, p < .001, Cohen’s d z = 1.32), suggesting that the between-movie boundary pattern may reflect a cognitive state qualitatively different from the state elicited by event boundaries during movie watching (e.g., attentional engagement; Song et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
“…One caveat to this conclusion is that we did not look for other factors that could have driven the different modalities differently. All videos were designed to communicate factual information related to science and technology, and not, for instance, evoke suspense or emotions 5,6,11,68 . So it is possible that we did not find other factors simply because we did not manipulate other factors with our experimental paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that fluctuations in functional connectivity of fMRI correlate with HRV 58 and can be used to measure attentional state on a time scale of minutes 59 . Activity of the “default-mode network” is more correlated across subjects when they report to be more engaged with the stimulus 60 and it is increased in more memorable moments of the narrative 16 . The precuneus, which is part of the default-mode network, shows elevated activity during periods of high ISC of the EEG 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, individuals who express this RSFC profile more so than others would be expected to attend more to movie clips, leading to increased levels of ISC. At the parcel level, we would expect ISC in different parcels to be associated with the same 1,618 RSFC edges that comprise the predictive network, as greater attention to the movie clips should lead to distributed increases in ISC (Ki et al, 2016; Regev et al, 2019; Song et al, 2020). Instead, we observed that ISC in different parcels was associated with many different patterns of RSFC.…”
Section: Discussionmentioning
confidence: 99%